High Dietary Cholesterol Masks Type 2 Diabetes‐Induced Osteopenia and Changes in Bone Microstructure in Rats. Issue 10 (9th September 2014) - Lapmanee, Sarawut; Charoenphandhu, Narattaphol; Aeimlapa, Ratchaneevan; Suntornsaratoon, Panan; Wongdee, Kannikar; Tiyasatkulkovit, Wacharaporn; Kengkoom, Kanchana; Chaimongkolnukul, Khuanjit; Seriwatanachai, Dutmanee; Krishnamra, Nateetip
Abstract: Type 2 diabetes mellitus (T2DM) often occurs concurrently with high blood cholesterol or dyslipidemia. Although T2DM has been hypothesized to impair bone microstructure, several investigations showed that, when compared to age‐matched healthy individuals, T2DM patients had normal or relatively high bone mineral density (BMD). Since cholesterol and lipids profoundly affect the function of osteoblasts and osteoclasts, it might be cholesterol that obscured the changes in BMD and bone microstructure in T2DM. The present study, therefore, aimed to determine bone elongation, epiphyseal histology, and bone microstructure in non‐obese T2DM Goto‐Kakizaki rats treated with normal (GK‐ND) and high cholesterol diet. We found that volumetric BMD was lower in GK‐ND rats than the age‐matched wild‐type controls. In histomorphometric study of tibial metaphysis, T2DM evidently suppressed osteoblast function as indicated by decreases in osteoblast surface, mineral apposition rate, and bone formation rate in GK‐ND rats. Meanwhile, the osteoclast surface and eroded surface were increased in GK‐ND rats, thus suggesting an activation of bone resorption. T2DM also impaired bone elongation, presumably by retaining the chondrogenic precursor cells in the epiphyseal resting zone. Interestingly, several bone changes in GK rats (e.g., increased osteoclast surface) disappeared after high cholesterol treatment as compared to wild‐type rats fed high cholesterol diet. In conclusion, high cholesterol diet was capable of masking the T2DM‐induced osteopenia and changes in several histomorphometric parameters that indicated bone microstructural defect. Cholesterol thus explained, in part, why a decrease in BMD was not observed in T2DM, and hence delayed diagnosis of the T2DM‐associated bone disease.